Positive solutions to a third order nonlocal boundary value problem with a parameter - Szajnowska, Gabriela; Zima, Mirosława (Wydawnictwa AGH, 2024)
We present some sufficient conditions for the existence of positive solutions to a third order differential equation subject to nonlocal boundary conditions. Our approach is based on the Krasnosel'skiĭ-Guo fixed point theorem in cones and the properties of the Green's function corresponding to the BVP under study. The main results are illustrated by suitable examples.
Opuscula Mathematica
Bibliogr. 282-283.
Keywords: boundary value problem; nonlocal boundary conditions; positive solution; cone